Systematic and continuous collection of patient-reported outcomes and experience in women with cancer undergoing mastectomy and immediate breast reconstruction: a study protocol for the Tuscany Region (Italy). Issue 1 (11th January 2021) - Ferrè, Francesca; De Rosis, Sabina; Murante, Anna Maria; Gilmore, Kendall Jamieson; Ghilli, Matteo; Mariniello, Donatella; Nuti, Sabina; Roncella, Manuela
Abstract : Introduction: Monitoring how patients feel and what they experience during the care process gives health professionals data to improve the quality of care, and gives health systems information to better design and implement care pathways. To gain new insights about specific gaps and/or strengths in breast cancer care, we measure patient-reported outcomes (PROs) and patient-reported experiences (PREs) for women receiving immediate breast reconstruction (iBR). Methods and analysis: Prospective, multicentre, cohort study with continuous and systematic web-based data collection from women diagnosed with breast cancer, who have an indication for iBR after mastectomy treated at any Breast Unit (BU) in Tuscany Region (Italy). Patients are classified into one of two groups under conditions of routine clinical practice, based on the type of iBR planned (implant and autologous reconstruction). Patient-reported information are obtained prior to and after surgery (at 3-month and 12-month follow-up). We estimate that there are around 700 annual eligible patients. Descriptive analyses are used to assess trends in PROs over time and differences between types of iBR in PROs and PREs. Additionally, econometric models are used to analyse patient and BU characteristics associated with outcomes and experiences. PREs are evaluated to assess aspects of integrated care along the care pathway. Ethics and dissemination: The study has been reviewed and obtained a nihil obstat from the Tuscan Ethics Committees of the three Area Vasta in 2017. Dissemination of results will be via periodic report, journal articles and conference presentations.